Achievement goals influence mastery experience via two paths in digital creativity games among elementary school students. (29th January 2018) - Yeh, Y.‐c.; Lin, C.S.
Abstract: Although cultivating creativity is greatly emphasized in elementary school education and that digital games can be a promising tool for improving creativity, little research has been conducted to identify and explore how player‐related factors might influence the learning outcomes of digital creativity games. This study identifies 3 individual traits pertaining to digital creativity game playing and examines how these determinants influence self‐efficacy and mastery experiences of creativity using structural equation modelling. The participants were 275 4th through 6th graders, and the employed method was inventory investigation. The findings reveal that the participants spend a large proportion of time playing digital games after school. Moreover, the results suggest that motivation for achieving both mastery goals and performance goals is crucial to enhancing self‐efficacy and achieving mastery experience in creativity. Additionally, such motivation might enhance mastery experience via two paths: the experience of flow states and the strengthening of self‐determination and self‐efficacy. The findings of this study shed light on the design of digital games for creativity training. Lay Description: What is already known about this topic: While mastery goals create high self‐efficacy and positive effects, performance goals elicit anxiety and self‐handicapping. Self‐efficacy can be improved through game‐based learning. Goal setting is critical to achieving mastery experience and flow experience. Flow experience leads to enhanced learning and exploratory behaviour. What this paper adds: Both mastery goals and performance goals can provide benefits and be pursued together. Identifying three individual traits pertaining to digital creativity game playing and examines how these determinants influence self‐efficacy and mastery experiences of creativity using structural equation modelling. Both mastery and the performance achievement goals have positive effects on the achievement of flow experience and the enhancement of self‐determination Flow experience contributes to the development of self‐efficacy and mastery experience while playing digital creativity games. Implications for practice and/or policy: Mechanisms for enhancing performance goals and mastery goals (or process goals) should be simultaneously considered when designing digital creativity games for children. Motivation might enhance mastery experience via two paths: the experience of flow states and the strengthening of self‐determination and self‐efficacy. Taking advantage of the ability of digital games to stimulate intrinsic motivation by providing an individually calibrated balance of challenge and skill is crucial for enhancing self‐efficacy and mastery experiences of creativity. Digital‐game playing is prevalent and popular among elementary school children; if well‐designed digital creativity games are provided, they can improve creative thinking tremendously.